The impact of the Covid-19 pandemic on postnatal depression: analysis of three population-based national maternity surveys in England (2014–2020) - Harrison, S; Quigley, MA; Fellmeth, G; Stein, A; Alderdice, F (Elsevier, 2023)
Background Few studies have evaluated postnatal depression before and during the Covid-19 pandemic using comparable data across time. We used data from three national maternity surveys in England to compare prevalence and risk factors for postnatal depression before and during the pandemic.